Economic Burden of Non-Alcoholic Steatohepatitis (NASH) Among Diabetic Population in Italy: Analysis and Perspectives - Torre E; Di Matteo S; Bruno GM; Martinotti C; Valentino MC; Testino G; Rebora A; Bottaro LC; Colombo GL (Dove Medical Press, 2022)
Enrico Torre,1 Sergio Di Matteo,2 Giacomo Matteo Bruno,3 Chiara Martinotti,2 Maria Chiara Valentino,2 Gianni Testino,4 Alberto Rebora,1 Luigi Carlo Bottaro,5 Giorgio Lorenzo Colombo3 1Diabetology and Metabolic Diseases Unit - ASL3, Genoa, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche S.r.l., Health Economics & Outcomes Research, Milan, Italy; 3Department of Drug Sciences, University of Pavia, Pavia, Italy; 4Unit of Addiction and Hepatology - ASL3, Genoa, Italy; 5General Direction, ASL3, Genoa, ItalyCorrespondence: Giorgio Lorenzo Colombo, Department of Drug Sciences, School of Pharmacy, University of Pavia, Italy, Email giorgio.colombo@unipv.itBackground: Aim of our study is to evaluate the economic impact of NASH among diabetic population in Italy and potential benefits of treatments that can slow the disease progression.Methods: A Markov model was conducted from the Italian National Healthcare System perspective reporting results at 3, 5, 10 and 15 years. The model included NASH and T2DM patients with all stages of fibrosis (F0-F3), compensated cirrhosis (CC), decompensated cirrhosis (DCC), hepatocellular carcinoma (HCC), liver transplant (LT), post-LT and death. A 1-year model cycle length was considered, with each patient passing through the stages and exiting the model when reached one of mortality states. Transition probabilities and annual cost related to health states were derived from published literature. Moreover, the model made it possible to develop a scenario analysis to simulate the impact of treatments capable of slowing the disease progression in phases F0-F4 (CC).Results: The results highlighted an economic burden of NASH in T2DM patients of approximately € 1.4 billion, € 3.1 billion, and € 9.4 billion, respectively, after 3, 5 and 10 years, reaching about € 17.3 billion after 15 years. The slowing down of the progression in the early stages of the disease (fibrosis F0-CC) has led to significant savings corresponding to € 2.3 billion at 15 years. These savings were generated by the reduction of the patients in the advanced stages of the disease, which is linked to a reduction in deaths, equal to 92,208 deaths avoided over a 15-year time horizon.Conclusion: Patients with NASH and T2DM reported an important burden in Italy. It is important to investigate the potential clinical and economic benefits of antidiabetic drugs that have been shown to be effective in preventing the transition to advanced disease, simultaneously acting on the therapeutic goals of diabetic disease.Keywords: non-alcoholic steatohepatitis, type 2 diabetes mellitus, burden of illness, treatment perspectives